Efektivitas Pengelolaan Alokasi Dana Desa dalam Pembangunan Fisik Di Desa Selebung Ketangga - Mirnawati; Nurul Huda; Ayatullah (Pendidikan Al-Gafari, 2024)
Village development is one of the matters that is an authority village. As implications from maintenance development that, of course just will need financing or sources reception village. One of the source reception villages namely the balancing fund finance central and regional areas received by inner districts/cities the division for every village shared in a way proportional namely at least 10% (ten percent) is called with the allocation of village funds. The purpose of the study This is to know the planning management allocation of village funds in building physically in Selebung Village Ketangga, to see the implementation management allocation of village funds in building physique village in Selebung Village Ketagga, and to know the supervision management allocation of village funds in development physique village in Selebung Village Steps. Type of research used in study This is a type of study descriptive with the use approach with study effectiveness allocation of village funds. Data collection techniques from the study This includes observation, interviews, and documentation. planning management Village Fund allocation in increase development physically in Selebung Village Ketangge Subdistrict Cracking has done government village with principle participatory implementation management allocation of village funds in building physical village in Selebung Village Steps. implementation management allocation of village funds in increased development physically in Selebung Village Steps Subdistrict Cracking East Lombok Regency has held government village with apply principle participatory supervision management allocation of village funds in development physical village in Selebung Village Steps. Supervised Selebung Village fund allocation Steps through administration, reports activities and reports monthly and annually.